Propranolol therapy for the management of oral lobular capillary hemangioma in a 2-year-old preschooler: A case report and review - Namita Kalra; Rishi Tyagi; Amit Khatri; Harsh Vijay Singh; Puja Sabherwal; Mayank Sharma (Wolters Kluwer Medknow Publications, 2020)
Lobular capillary hemangioma (LCH), a histological variant of pyogenic granuloma (PG) is an inflammatory hyperplasia commonly seen on oral mucosa as a reaction to local irritants, trauma or hormonal influences. The term "PG" is a misnomer as it is neither pus filled nor representative of a granuloma histologically. It is an inflammatory lesion composed of proliferating vascular, fibrous, and inflammatory tissue. The benign tumor has varied clinical and histopathological presentations and occurs frequently on the gingiva in the oral cavity. The article presents a case report where 2-week propranolol therapy was used to manage oral LCH (with a rare site of presentation) in a 2-year-old preschooler with a 9-month follow-up showing no recurrence followed by review of literature.